The prevalence of nasal colonization of Staphylococcus aureus and it's antibiotic susceptibility patterns among pre-clinical and clinical students at Universiti Malaysia Sabah - Norfarid Irfan Mohd Subri (2017)
This study was a cross-sectional descriptive study to determine the prevalence of nasal colonization of Staphylococcus aureus (S. aureus) among pre-clinical and clinical medical students and nursing students attending Faculty of Medicine and Health Sciences at the Universiti Malaysia Sabah (UMS). From April 2013 to November 2013, nasal swabs were collected from anterior nares of 449 students. Nasal swabs were inoculated on Mannitol Salt Agar (MSA) for isolation of Staphyococcus followed by Gram stain and identification of S. aureus by coagulase test using Staphylase test kit and tube coagulase test. Antibiotic susceptibility test was done on all S. aureus isolates using Kirby-Bauer method and six antibiotics discs penicillin, oxacillin, erythromycin, clindamycin, tetracycline and trimethroprim-sulfamethoxazole were included. Cefoxitin susceptibility was also performed to detect Methicillin Resistant Staphylococcus aureus (MRSA). S. aureus isolates were also tested with Slidex ® MRSA Detection kit (bioMérieux® SA) to detect Penicillin-binding protein 2a product of MRSA. The results showed that the prevalence of nasal colonization of S. aureus among 449 subjects was 31.0%, all were MSSA and none of the isolates were MRSA. Antibiotic susceptibility testing revealed that all 139 S. aureus isolates were sensitive to oxacillin, trimethroprim-sulfamethoxazole and cefoxitin, whereas 116 (83.5%), 1 (0.7%), 3 (2.2%) and 24 (17.3%) were resistant to penicillin, erythromycin, clindamycin and tetracycline respectively. This study also found out that the potential association of S. aureus colonization was not significant to all factors except the university program of students (p<0.046). In conclusion, the prevalence of S. aureus nasal colonization among pre-clinical and clinical students at UMS was 31.0%. No MRSA was detected and the S. aureus isolates were highly resistant to penicillin.